Aqueous Synthesis of the Tiopronin-Capped Gold Nanoclusters/Nanoparticles with Precise Size Control via Deprotonation of the Ligand - Daekyung Kang; Changhee Son; Hakseon Lee; Hongsik Park; Taewan Kim; Jonghoo Park (Applied Sciences, 2022)
Gold nanoparticles have led to numerous advances in nanomaterial-based sensors and biomedical technologies owing to their chemical inertness and outstanding physiochemical and optical properties. Gold nanoparticles are still considered one of the most promising types of nanomaterials in various biomedical fields, including drug delivery, cancer therapy, biomolecule detection, and high-accuracy diagnosis. Surface functionalization of gold nanoparticles with various ligands modifies the physicochemical properties of the surface, thereby improving the biocompatibility and uptake efficiency of a living system. Tiopronin, one of the most commonly used ligands for gold nanoparticles, has both thiol and carboxyl functional groups that can be easily attached to various biomolecules. However, the conventional method of synthesizing tiopronin-capped gold nanoclusters using methanol and acetic acid as a solvent requires a laborious and time-consuming dialysis process to remove methanol and acetic acid. In this study, we demonstrate a novel and simple aqueous synthesis method to obtain tiopronin-capped gold nanoclusters/nanoparticles with precise size control in the sub-nanometer to nanometer range. The main advantage of our synthesis method is that it does not require a dialysis process because it uses water as a solvent. The boron byproduct produced during the synthesis can be removed with a simple volatilization process. Moreover, we characterized the physical morphologies, photoelectronic properties, hydrodynamic size, and crystal structure of the tiopronin-capped gold nanoclusters/nanoparticles using transmission electron microscopy, spectrophotometry, fluorescence spectrometry, dynamic light scattering, zeta potential, and X-ray diffraction.